Ethics and values in social research - Ransome, Paul (Basingstoke, Hampshire, [England] Palgrave Macmillan, 2013)
"Ethical responsibility has intellectual and practical implications for social researchers. This book explores a range of issues, theories and questions, enabling readers to reflect upon, understand and critique these with confidence. With helpful examples and a glossary of terms, it is essential reading for new and experienced researchers alike."--Publisher's website.
Introduction: Themes and Debates -- Social Values and Social Research: The Collective Good, Life and Liberty, and Reason -- Social Research and Professional Codes of Ethics -- The Intellectual and Philosophical Underpinnings of Social Research -- The values of the Researcher and Evaluation Research -- Critical Approaches in Social Research: Critical Realism and Value Standpoint Social Research -- Making it Personal: Action Research, Practitioner Research and Self-reflexive Practice -- Social Research and Social Policy.
Includes bibliographical references (pages 178-183) and index.
Keywords: Social sciences -- Research -- Moral and ethical aspects; Social scientists -- Professional ethics